TAX REVENUE PATTERN OF BORSAD TALUKA PANCHAYAT (International Journal of Food and Nutritional Sciences, 2022)
Borsad is famous town known by Satyagraha done by Sardar Vallabhbhai Patel. There are 8 blocks (Taluka) of Anand District. Borsad is one of the block of these 8 blocks of Anand District. It is just 17 km far from Anand. There are 2 towns and 64 villages in Borsad Taluka. Farmers of Borsad Taluka grow tobacco, bananas, cotton, barley and other seasonal commodities. During 1922-23 Borsad Taluka's people fought satyagrahe against Britishers in the leadership of Serdar Vallabhbhai Patel. The satyagraha was fought due to unlegal tax loaded by Britishers. Britisher's accused that people of Borsal Taluka are helping to outlaws, But in fact police in the Borsad taluka were helping to these outlaws. At last people won the satyagraha and Britishers had to withdraw the law of unlegal tax.